In Situ Formation of Steroidal Supramolecular Gels Designed for Drug Release - Hana Bunzen (Molecules, 2013)
In this work, a steroidal gelator containing an imine bond was synthesized, and its gelation behavior as well as a sensitivity of its gels towards acids was investigated. It was shown that the gels were acid-responsive, and that the gelator molecules could be prepared either by a conventional synthesis or directly in situ during the gel forming process. The gels prepared by both methods were studied and it was found that they had very similar macro- and microscopic properties. Furthermore, the possibility to use the gels as carriers for aromatic drugs such as 5-chloro-8-hydroxyquinoline, pyrazinecarboxamide, and antipyrine was investigated and the prepared two-component gels were studied with regard to their potential applications in drug delivery, particularly in a pH-controlled drug release.